2005
DOI: 10.1002/marc.200500291
|View full text |Cite
|
Sign up to set email alerts
|

Improved Pharmacokinetics Properties for Catalase by Site‐Specific Glycosidation with Aminated Dextran

Abstract: Summary: Catalase was chemically modified with an end‐group aminated dextran derivative via a carbodiimide catalyzed reaction. The enzymatic activity of catalase was increased after glycosidation with 4 mol of polymer. This modification improved the pharmacokinetic behavior of catalase, increasing by 7.8‐ and 20‐fold the plasma half‐life times for the α and β phases, and reducing by 176‐fold the total clearance after intravenous administration in rats.Schematic of the catalase dextran conjugate synthesized her… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 20 publications
0
10
0
Order By: Relevance
“…The conjugation yield of amine was determined by 1 H nuclear magnetic resonance (NMR) spectroscopy. 16 N-hydroxysuccinimide PLGA (PLGA-NHS) was prepared as follows. PLGA 500 mg was dissolved in dichloromethane, and 1.5 equivalents of N,N′-dicyclohexyl carbodiimide and N-hydroxysuccinimide were added.…”
Section: Synthesis Of Dexblg Block Copolymermentioning
confidence: 99%
“…The conjugation yield of amine was determined by 1 H nuclear magnetic resonance (NMR) spectroscopy. 16 N-hydroxysuccinimide PLGA (PLGA-NHS) was prepared as follows. PLGA 500 mg was dissolved in dichloromethane, and 1.5 equivalents of N,N′-dicyclohexyl carbodiimide and N-hydroxysuccinimide were added.…”
Section: Synthesis Of Dexblg Block Copolymermentioning
confidence: 99%
“…Block copolymers composed of dextran and other polymers have also been reported. Pérez et al [8] reported the improved pharmacokinetic properties of catalase-conjugated dextran. The catalase-conjugated dextran has similar architecture to block copolymer.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, dextran is known to be taken up in the intestinal tract in a specific manner [7]. Pérez et al [8] reported that catalaseconjugated dextran increases the enzymatic activity and bioavailability.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, intravenous (i.v.) administration of the conjugate to lean rats illustrated a markedly improved PK profile, with a 20‐fold longer elimination half‐life (from 0.8 to 16 h), a 171‐fold increased exposure (from 1.8 to 307 U h mL −1 ), and a 176‐fold decreased clearance (from 120 to 0.68 mL min −1 ) …”
Section: Carbohydrate Polymersmentioning
confidence: 99%